2018
DOI: 10.1371/journal.pone.0205843
|View full text |Cite
|
Sign up to set email alerts
|

Species- and developmental stage-specific effects of allelopathy and competition of invasive Impatiens glandulifera on co-occurring plants

Abstract: BackgroundImpacts of invasive species on native communities are often difficult to assess, because they depend on a range of factors, such as species identity and traits. Such context-dependencies are poorly understood yet, but knowledge is required to predict the impact of invasions.Materials and methodsWe assessed species- and developmental stage-specificity of competitive and allelopathic effects of the invasive plant Impatiens glandulifera on different developmental stages of four native plant species. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The reason could be a seasonally varying allelopathic effect of I. glandulifera because it is known, that in spring I. glandulifera has a higher content of the allelopathic compound 2-MNQ compared to summer (Ruckli et al 2014a). In a previous experimental study we showed that I. glandulifera has a species-specific allelopathic and competitive impact on native plants especially in the seedlings-and juvenile-stage (Bieberich et al 2018). Furthermore, cover of I. glandulifera from the previous sum-mer 2016 affected species composition in spring while it did not affect the resident community in summer 2016 itself.…”
Section: Plant Communities In Summer and Spring Were Affected Differementioning
confidence: 89%
See 2 more Smart Citations
“…The reason could be a seasonally varying allelopathic effect of I. glandulifera because it is known, that in spring I. glandulifera has a higher content of the allelopathic compound 2-MNQ compared to summer (Ruckli et al 2014a). In a previous experimental study we showed that I. glandulifera has a species-specific allelopathic and competitive impact on native plants especially in the seedlings-and juvenile-stage (Bieberich et al 2018). Furthermore, cover of I. glandulifera from the previous sum-mer 2016 affected species composition in spring while it did not affect the resident community in summer 2016 itself.…”
Section: Plant Communities In Summer and Spring Were Affected Differementioning
confidence: 89%
“…The cover of both species correlated negatively, and according to the SEM they were favored by the same environmental conditions. Experimental studies confirm that U. dioica is negatively affected by I. glandulifera and that this effect is larger than vice versa (Tickner et al 2001, Gruntman et al 2014, Bieberich et al 2018.…”
Section: Impatiens Glandulifera Had No Impact On Plant Diversity But mentioning
confidence: 97%
See 1 more Smart Citation
“…Impatiens glandulifera (an invasive species) produces 2-methoxy-1, 4-naphthoquinonw (2-MNQ), which is reckoned as an important allelochemical (Ruckli et al 2014). Recently, it was found not only negatively affecting native plants but also the plants from the same species in neighbors (Bieberich et al 2018).…”
Section: Interspecific and Intraspecific Interactionmentioning
confidence: 99%
“…Several studies have reported that I. glandulifera has a negative influence on ecosystems and ecosystem services, such as plant diversity (Kiełtyk and Delimat 2019), soil fungal communities (Gaggini et al 2019;Pattison et al 2016;Ruckli et al 2016), and terrestrial invertebrates (Seeney et al 2019). Allelopathic components of I. glandulifera may also negatively affect native vegetation (Bieberich et al 2018). In a riparian area in northwest Switzerland, Greenwood and Kuhn (2014) found that erosion was greater from sites invaded by I. glandulifera compared with sites with native vegetation.…”
Section: Introductionmentioning
confidence: 99%